Acute pancreatitis and relative polycythaemia: a case series - Modi, Shraddha; Subbarayan, Boopathi; Subbaraj, Saravanakumar; Tirougnanassmbandamourty, Tirouaroul; Smile, S. Robinson (International Surgery Journal, 2020)
Relative polycythaemia is an apparent rise in erythrocyte level in the blood. However, the underlying cause is reduced blood plasma. Relative polycythaemia is often caused by loss of body fluids seen in conditions such as burns, dehydration and stress manifesting itself as a raised Haemoglobin or haematocrit. This case series presents a clinical summary of three patients with acute pancreatitis (AP) and relative polycythaemia due to reduction in plasma volume as a result of intravascular volume depletion as demonstrated by increase in haemoglobin and haematocrit. Haem concentration may be considered as a marker for acute severe pancreatitis and correcting the volume depletion by adequate fluid improves the outcome of AP as seen in all our three patients.